2013
DOI: 10.1088/0964-1726/22/9/095019
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric energy harvesting from traffic-induced bridge vibrations

Abstract: Abstract. This paper focuses on energy harvesting of traffic-induced vibrations in bridges. Using a pre-stressed concrete highway bridge as a case study, in situ vibration measurements are presented and analyzed. From those results, a prototype of cantilever piezoelectric harvester was designed, tested, and modeled. Even though the considered bridge vibrations are characterized by small amplitude and a low frequency (i.e. below 15 Hz), it is shown that mean power of the order of 0.03 mW can be produced, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 13 publications
1
104
0
1
Order By: Relevance
“…A piezoelectric cantilever-type BEH [27] is devised for narrow band vibrations. In the harvester, two piezoelectric patches are bonded (near the clamped end of the beam) to the top and bottom surfaces of the steel cantilever beam; however, a proof mass is bonded to the free end of the beam to tune the BEH at the resonant frequency of 14.5 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…A piezoelectric cantilever-type BEH [27] is devised for narrow band vibrations. In the harvester, two piezoelectric patches are bonded (near the clamped end of the beam) to the top and bottom surfaces of the steel cantilever beam; however, a proof mass is bonded to the free end of the beam to tune the BEH at the resonant frequency of 14.5 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the proposed harvester is compared to the results of existing research studies which implement their harvesters in a cantilever system under a similar range of excitation frequency and acceleration. The existing research works [35][36][37][38][39][40][41][42] produced a volume power density of (0.9 × 10 −2 -20 × 10 −2 ) µW/mm 3 under the excitation frequency of (1.4-100) Hz and the acceleration of (0.2-10) ms −2 . The current work produces a power density of 0.10 µW/mm −3 at a frequency and acceleration of 30 Hz and 0.4 ms −2 , respectively.…”
Section: Resistance (Kω)mentioning
confidence: 99%
“…A separate venture [11] employed a cantilever piezoelectric harvester to exploit the energy from vibrations produced by traffic movement over bridges. It has been observed that by maintaining a voltage between 1.8 and 3.6 V under a frequency lower than 15 Hz, mean power of as much as 0.03 mW can be generated.…”
Section: Related Workmentioning
confidence: 99%